2016
DOI: 10.1186/s12879-016-1540-0
|View full text |Cite
|
Sign up to set email alerts
|

Morbimortality in adult patients with septic arthritis: a three-year hospital-based study

Abstract: BackgroundThe objective of this ambispective study was to determine outcomes and associated factors for adult patients with confirmed septic arthritis (SA).MethodsAll adult patients admitted to Amiens University Hospital between November 2010 and December 2013 with confirmed SA were included in the study. Patients with prosthetic joint infections were excluded. A statistical analysis was performed in order to identify risk factors associated with a poor outcome (including mortality directly attributable to SA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
64
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 29 publications
(58 reference statements)
6
64
2
1
Order By: Relevance
“…1,2 Rates of mortality as high as 10-15%, [3][4][5][6][7][8] osteomyelitis in 8%, 8 and a subjective poor outcome in 20-30% of cases have been reported. 3,6,[8][9][10] The true rate of adverse outcomes has remained uncertain as previous studies have had a number of limitations, such as heterogenous inclusion criteria and inconsistent reporting of outcomes. No study has been joint specific and most studies included patients with small joint infection, prior surgery or joint arthroplasty, and outcomes were reported at inconsistent periods of follow up.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Rates of mortality as high as 10-15%, [3][4][5][6][7][8] osteomyelitis in 8%, 8 and a subjective poor outcome in 20-30% of cases have been reported. 3,6,[8][9][10] The true rate of adverse outcomes has remained uncertain as previous studies have had a number of limitations, such as heterogenous inclusion criteria and inconsistent reporting of outcomes. No study has been joint specific and most studies included patients with small joint infection, prior surgery or joint arthroplasty, and outcomes were reported at inconsistent periods of follow up.…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus aureus remains the top etiologic cause of SA (2). The attributed morbidity and mortality is substantial; treatment is of critical benefit to avert consequences (3). Culture-based diagnosis is not helpful in a proportion of patients, hence early antibacterial treatment to prevent permanent joint damage remains a challenge (1,3).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported data on the incidence of SA in the Western Europe and USA, which respectively have been between 2 and 10 per 100,000 patient-years [2]. …”
Section: Introductionmentioning
confidence: 99%